Preparation and Electrochemical Performance of Ti2Nb10O29/Ag Composite as Anode Materials for Lithium Ion Batteries. (1st November 2017) - Mao, Wutao; Liu, Kecheng; Guo, Ge; Liu, Guangyin; Bao, Keyan; Guo, Jiali; Hu, Min; Wang, Weibo; Li, Beibei; Zhang, Kailong; Qian, Yitai
Graphical abstract: Abstract: In lithium ion batteries anode material is very crucial. Exploring the high-performance anode materials remains a great challenge. Here, Ti2 Nb10 O29 /Ag composite was obtained. Electrochemical measurements demonstrate that Ti2 Nb10 O29 /Ag composite shows good electrochemical performance than pure Ti2 Nb10 O29, mostly due to enhanced electronic conductivity after Ag-coating. The specific capacities of Ti2 Nb10 O29 /Ag composite can be as high as 253 and 173 mAh g −1 at 1 and 10C, respectively, and the specific capacity is 132 mAh g −1 at 20C. Moreover, the Ti2 Nb10 O29 /Ag composite exhibited excellent cyclic stability, even after 500 cycles, its specific capacity at 10C still stabilized at a large value of 142 mAh g −1, which was in sharp contrast to the corresponding values of pure Ti2 Nb10 O29 (68 mAh g −1 ). The high electrochemical performance demonstrated that Ti2 Nb10 O29 /Ag composite is highly promising anode materials for Li-ion batteries.